Marketing essentials - Kotler, Philip (New Jersey : Prentice-Hall, 1984)
The subject is far too fascinating to be displayed only in skeletal form.
1. Social foundations of marketing : meeting human needs -- 2. The marketing management process - 3. Marketing research and information systems -- 4. The marketing environment -- 5. Consumer markets and consumer buyer behavior.
Includes bibliographical references and index.
Keywords: MARKETING